2017
DOI: 10.1038/s41598-017-07000-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutations Driving Airborne Transmission of A/H5N1 Virus in Mammals Cause Substantial Attenuation in Chickens only when combined

Abstract: A/H5N1 influenza viruses pose a threat to human and animal health. A fully avian A/H5N1 influenza virus was previously shown to acquire airborne transmissibility between ferrets upon accumulation of five or six substitutions that affected three traits: polymerase activity, hemagglutinin stability and receptor binding. Here, the impact of these traits on A/H5N1 virus replication, tissue tropism, pathogenesis and transmission was investigated in chickens. The virus containing all substitutions associated with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…Our results suggest that the 2.3.4.4 clade of H5N6 viruses is not likely to spread in the human population and would need to further adapt to humans to acquire a transmissible phenotype; however, those rare infections are likely to result in severe disease. A previous study conducted in chickens showed that although acquisition of some human adaptations may have a negligible effect on virus replication, viruses containing multiple mammalian adaptation markers might be highly attenuated in birds suggesting that viruses possessing the required combination of molecular adaptations necessary for airborne transmission are not likely to emerge from birds 50 ; as such, a mammalian intermediate host may be necessary for full adaptation of an avian influenza virus to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the 2.3.4.4 clade of H5N6 viruses is not likely to spread in the human population and would need to further adapt to humans to acquire a transmissible phenotype; however, those rare infections are likely to result in severe disease. A previous study conducted in chickens showed that although acquisition of some human adaptations may have a negligible effect on virus replication, viruses containing multiple mammalian adaptation markers might be highly attenuated in birds suggesting that viruses possessing the required combination of molecular adaptations necessary for airborne transmission are not likely to emerge from birds 50 ; as such, a mammalian intermediate host may be necessary for full adaptation of an avian influenza virus to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, the best intentions can result in a health disaster, such as the deployment of a peacekeeping force and the cholera outbreak in Haiti in 2010 [ 106 ] or the project of spreading some modified mosquitoes to fight against malaria [ 107 ]. Technology allows us to modify organisms specifically leading to the reconstitution of the Spanish Influenza virus [ 108 ] or to unexpected results as a test for a new poxvirus vaccine resulted with an ultra-virulent strain able to neutralise the immune system [ 109 ] or, during research experiments mimicking natural phenomenon, the generation of highly-resistant B. anthracis spores [ 110 ] and viruses acquiring airborne transmission [ 111 ]. Nowadays, these widely used technics appear to be almost obsolete in comparison with the new capacities of gene synthesis: a horsepox virus has been reconstructed using only internet-bought sequences [ 112 ], and a new bacterium has been created de novo in a laboratory [ 113 ].…”
Section: Dimensioning the Global Preparednessmentioning
confidence: 99%
“…NS1-deleted vaccine candidates with HA-activation pH values of 5.5–5.8 have infectivity and immunogenicity higher than those of related variants triggered at pH 6.0–6.3 (36, 37). In H5 viruses with relatively unstable HA proteins, stabilizing mutations have been shown to increase upper respiratory tract replication in mice and ferrets (3840) and to enable gain-of-function transmissibility in ferrets (13, 14); however, these mutations decrease the replication, virulence, and transmissibility in avian species (4143).…”
Section: Introductionmentioning
confidence: 99%